Highly efficient Z-scheme photocatalysts of Ag/AgIn5S8 decoration on surfaces with high exposure (040) BiVO4 for enhanced photocatalytic performance. (December 2022) - Zhou, Yi; Chen, Zhiyue; Li, Jiaxin; Xiang, Minghui; Zhou, Yinghong; Niu, Jiangtao; Zhang, Jin
Abstract: Design and construction of a heterojunction structured photocatalyst with efficient electron transfer is of great significance. In this work, we prepared a unique Z-scheme Ag/Agln5 S8 /BiVO4 photocatalyst of which BiVO4 has highly exposed (040) crystal facets. Ag as an electronic medium to build a special and efficient electron transfer path. In addition, the surface plasmon resonance effect of Ag improves the sunlight utilization of photocatalyst, and Ag as an electron transport medium and co-catalyst enhances the photocatalytic ability of the photocatalyst. Under optimum reaction conditions, the loading of AgIn5 S8 is 30%, the reaction rate constants of tetracycline degradation over Ag/BA-30% were 1.96 and 5.58 times of pure BiVO4 and AgIn5 S8 . The possible Z-scheme electron-hole pair transfer mechanism was presented through the capture experiment. It is suggested that ·O2 −, h + and ·OH are engaged in the degradation of TC. And the prepared photocatalysts were proved to have a potential application value after four consecutive cycles. Highlights: The Ag/Agln5 S8 /BiVO4 (040) Z-scheme heterojunction photocatalyst has been first prepared. Highly exposed (040) facet of BiVO4 promotes photogenerated carrier separation efficiency. Ag/Agln5 S8 /BiVO4 (040) has better electron transfer path and light absorption ability. Ag nanoparticles as electron mediator and co-catalyst enhances the photocatalytic performance of the photocatalyst. The enhanced mechanism of photocatalytic degradation of TC was discussed.